Explicating peer feedback quality and its impact on feedback implementation in EFL writing - He, Wenjing; Gao, Ying (Frontiers in Psychology, 2023)
Introduction Although it is commonly acknowledged that peer feedback quality is crucial to the success of peer review, there is a lack of consensus on how it could be determined. More importantly, how feedback quality interacts with other factors like feedback features and focus, and ultimately influences peer feedback implementation remains insufficiently investigated. Methods The present study examined peer feedback quality and its impact on Chinese students’ feedback implementation in two argumentative writing tasks. Peer feedback quality was measured according to a self-designed two-dimensional measurement scale: accuracy and revision potential. Results Quantitative analyses of 5,606 implementable idea units of feedback and 440 writing drafts by 110 students revealed that feedback accuracy was at a medium level and revision potential was at a low level, with accuracy demonstrating stronger predictive power on implementation; the predictive strengths of feedback accuracy and revision potential were strongest when feedback features and focus were considered; the overall peer feedback quality was low and medium-quality feedback was implemented most frequently; feedback quality significantly and most strongly predicted implementation in combination with feedback features and focus. Discussion The study highlights the importance of future instructions in training students to provide and implement high-quality feedback with good accuracy and high revision potential.